2023
DOI: 10.3892/br.2023.1633
|View full text |Cite
|
Sign up to set email alerts
|

Ring finger protein 215 is a potential prognostic biomarker involved in immune infiltration and angiogenesis in colorectal cancer

Abstract: The prognostic value of ring finger protein 215 (RNF215) in colorectal cancer (CRC) is unclear. Herein, the present study aimed to investigate the precise value of RNF215 based on CRC datasets from The Cancer Genome Atlas (TCGA) and clinical cases. CRC patient data was collected from TCGA and clinical samples from the Department of Pathology, Shanghai Fifth People's Hospital, Fudan University (Shanghai, China). Logistic regression analysis was used to investigate the correlations between RNF215 and clinicopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The present preliminary study showed that the expression of RNF215 was significantly higher in CRC tumor tissues than in normal tissues. RNF215 may contribute to the development and progression of CRC by participating in CRC-associated signaling pathways, such as the Kyoto Encyclopedia of Genes and Genomes MAPK signaling pathway, the WP RAS signaling pathway, and the WP PI3KAKT signaling pathway (20). However, the associations between RNF215 expression and KRAS, NRAS, BRAF and PIK3CA mutations in patients with CRC have not been reported.…”
Section: Association Of Kras Nras Braf and Pik3ca Gene Mutations With...mentioning
confidence: 99%
“…The present preliminary study showed that the expression of RNF215 was significantly higher in CRC tumor tissues than in normal tissues. RNF215 may contribute to the development and progression of CRC by participating in CRC-associated signaling pathways, such as the Kyoto Encyclopedia of Genes and Genomes MAPK signaling pathway, the WP RAS signaling pathway, and the WP PI3KAKT signaling pathway (20). However, the associations between RNF215 expression and KRAS, NRAS, BRAF and PIK3CA mutations in patients with CRC have not been reported.…”
Section: Association Of Kras Nras Braf and Pik3ca Gene Mutations With...mentioning
confidence: 99%